Assessment of Role s100A7 and Eotaxin (CCL24) in Patients with Atopic Dermatitis in Babylon City - Muhammad, Mahmoud; Juda, Thanaa; Al-Fadili, Zina (Journal of Biomedicine and Biochemistry, 2023)
Background Atopic dermatitis (AD) is a chronic, diverse, inflamma- tory skin disease that generally starts in infancy and lasts into adulthood. Tcell-driven inflammation, mostly through T helper (Th) 2- and Th17- derived cytokines, which are controlled by the Janus kinase (JAK) signal- ing pathway, is critical to AD. S100a7 and eotaxin(ccl24) were measured in serum samples.Objective Finding diagnostic, prognostic, and predictive biomarkers that can be used to diagnose atopic dermatitis patients early in the course of the disease is the goal of the current study. It also aims to determine changes in s1007a and eotaxin as a biomarker in atopic dermatitis patients and the study of these markers to give advice on how to treat AD.Material and methods  The samples were obtained from the derma- tology clinic’s registered patients at Al-Musayyib General Hospital, Al- Imam Al-Sadiq Hospital, and Murjan Teaching Hospital between October 1 and November 1, 2022. Blood samples were utilized to analyze the bio- chemical properties of the serum, such as s100a7 and eotaxin(ccl24). were assessed for patients using the ELISA technique. The statistical analysis was carried out using SPSS software.Results  Results of the examination of the eotaxin biomarker in the pa- tient group with atopic dermatitis were substantially better than those in the control group (p ≤ 0.05), and the s100a7 biomarker increased in the patient groups compared to the control group (p ≤0.05).Conclusion  Patients with atopic dermatitis had considerably higher levels of every parameter compared to healthy persons.